Endophytic bacteria enhance the growth and salt tolerance of rice under saline conditions - Quang Trung DO; Anh The LUU; Tien Chuong NGO (Acta Agriculturae Slovenica)
Developing biostimulants from salt-tolerant plant growth-promoting (PGP) bacteria is an emerging strategy for sustainable agriculture in the context of increasing soil salinization. This study aimed to isolate endophytic bacteria (EB) capable of promoting rice seed germination and seedling growth at different NaCl concentrations. Nine salt-tolerant EB strains were isolated and two, ST.6 and ST.8, with the rice seed promoting effect 99.3 and 99.7 %, respectively, were selected and identified as Pantoea dispersa and Burkholderia cenocepacia, respectively. ST.6 showed a higher value of the activity of phosphatase (617 mg P ml-1), production of indole-3-acetic acid (19.7 µg IAA ml-1), the activity of 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase (13.5 µmol mg−1 protein h−1), and production of siderophore (76.3 %). Especially, rice seedlings inoculated with strain ST.6 showed a significant improvement in root length (58.95 %), shoot length (16.6 %), dry biomass (7.0 %), the content of chlorophyll (46.2 and 57.1 % for chlorophyll a and b, respectively), carotenoids (22.2%), and proline (19.0 %). A decrease in antioxidant enzyme activities was also observed in the rice seedlings inoculated with either ST.6 or ST.8 strain under salt stress. Furthermore, the salt stress condition enhanced the colonization of roots by both studied endophytic bacteria. More experiments should be done to develop endophytic bacteria ST.6 and ST.8 as efficient bio-inoculants.